The thinking heart : essays on Israel and Palestine - Grossman, David (Vintage International, 2024)
"Just after October 7th 2023, David Grossman, a longtime voice of moral clarity in the Middle East, retreated inward to ask himself anew these urgent questions about his beloved nation: How could this massacre have happened? How could the Netanyahu government, tangled in its web of scandals, have failed to protect its citizens? And did October 7 and the senseless war that has followed take with it the last hope of a two-state solution? In these eleven essays, which appeared at key moments when Grossman wanted to hold the government accountable, he traces the failures leading up to that day and the ensuing war, enabled and abetted by a morally bankrupt party clinging to power. He documents the struggle between those committed to conflict, and those who want to live in peace and equality with their neighbors. He asks what the meaning and purpose of a Jewish state can be when the core values of Judaism are cast aside, and how his people, so accustomed throughout history to being in the minority, have not proved able to exist as a majority with the dignity and humanity that the job demands. Ultimately, Grossman arrives at the most important question of all: Will there ever be a lasting peace in the region?"--